Comparison between oxytocin, ergometrine and misoprostol in active management of the third stage of labour: a randomized controlled trial - Rahim, Abubaker Y. H. Abdel; Ounsa, Mohamed A. A. Gadir E.; Albarakati, Rayan G.; Mohamed, Elsadig Y.; Abdalla, Sawsan M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the present study was to compare the effectiveness of sublingual misoprostol, intravenous infusion of oxytocin, and intravenous infusion of Ergometrine in reducing blood loss during the third stage of labor. Methods: This is a no-random trial study conducted in in Ribat University Hospital, Khartoum among 150 laboring ladies with a healthy singleton pregnancy. After obtaining their written informed consent to participate in the study, they were randomly assigned to one of three possible treatment groups: 400 μg of sublingual misoprostol; 10 IU of intravenous infusion oxytocin; and 0.5 mg of intravenous infusion of Ergometrine. Blood loss was estimated by weighing the collected blood and converting the weight to milliliters. Results: The shortest mean duration of the third stage of labor was seen in patients who received misoprostol (3.89±0.37 min), followed by oxytocin (4.6±0.9 min), and Ergometrine (5.45±0.9 min). The lowest mean blood loss was seen in the patients who received 400 µg misoprostol (168.36±24.83 ml), followed by those who received 10 IU oxytocin (205.56±34.82 ml), and 0.5 mg Ergometrine (214.49±35.97 ml). Conclusions: Present study showed that 400 µg sublingual misoprostol was more effective than the conventional parenteral uterotonics in reducing the amount of the blood loss during the third stage of labor and has comparable effect to that of 10 IU intravenous oxytocin in shortening the duration of third stage of labor. It also showed that the use of misoprostol reduces the need for extra-uterotonics and blood transfusion.